Stimulants, hindrances and gauges of regional development – theoretical analysis (Economic and Political Thought, 2015)
The article focuses on the problems of stimulant, hindrances and regionaldevelopment measures. A broad theoretical analysis presented in this paper,as stimulants defines pro-development factors through which socio-economicdevelopment is possible. On the other hand hindrances are factors thatinhibit the development of regions or make it impossible. In a study on thedevelopment and competitiveness of regions, regional development measuresalso play an important role. They are a conglomeration of various indicators(economic, social, environmental) that allow indicate the strengths andweaknesses of the regions, identify opportunities and threats studied areasand allow for conducting comparative analyzes. This article contains researchmodel which is constructed based on the analysis of individual stimulant andhindrances of development and regional development measures which arewidespread in the literature, constituting their refresh and extension.